Diferencias en el desempeño del ejecutivo central y la agenda viso-espacial en el estudiantado de preescolar costarricense según su nivel socioeconómico y sexo - Alvarado Navarro, Dahiana; Chacón Jiménez, Roberto (Innovaciones Educativas, 2022)
This article compares the differences in the performance of the central executive and the visualspatial storage in preschool children according to their socioeconomic level, through the work with 60 preschool children between the ages of five years and three months old and six years and two months old of different socioeconomic levels: 30 of low and medium-low socioeconomic status; and 30 of a high socioeconomic level. It also compares performance by gender. For the evaluation of the central executive, the Symbol Search subtest of the WPPSI-III was used, while the visual-spatial sketchpad was measured through the Cues subtest of the WPPSI-III. At the socioeconomic level, a questionnaire measured their parents’ or legal guardians’ monthly income. The research approach is quantitative because the study variables were measured numerically. The comparison made with a Student’s t-test reveals that preschool children with a high socioeconomic level obtained higher scores in both subtests. Nonetheless, with no distinction by sex. Therefore, according to the analyzed sample, it was concluded that in the Costa Rican context, factors such as the monthly income of the parents or legal guardians, the place of residence, the parent’s educational level, and the access to public or private education proved statistically significant for the performance of tasks related to the visual-spatial storage and the central executive in preschoolers. For its part, sex does not affect the performance of the visuospatial agenda and the central executive.